Baccarat gamblers follow trends rather than adhere to the gambler's fallacy: Analyses of field data from a casino - Hiroyuki Muto; Ryusuke Nakai; Toshiya Murai; Sakiko Yoshikawa; Nobuhito Abe (Acta Psychologica, 2025)
This study investigated the cognitive biases underlying baccarat gambling behaviors through an analysis of 17,970,830 games played by 6625 customers in a casino. Baccarat, a popular high-stakes game in East Asia, involves predicting the outcome of two hands, where the results are inherently unpredictable, similar to the structure of games such as roulette. In contrast to existing theories predicting the emergence of the gambler's fallacy—or negative recency—when the outcome generation mechanism is clearly random, most baccarat gamblers exhibit the opposite bias, demonstrating a tendency toward positive recency. Specifically, customers increasingly placed bets on future outcomes to match past consecutive outcomes as streaks grew longer. This trend-following behavior diminished when streaks were interrupted, ruling out explanations based on the “hot outcome” fallacy, which is typically associated with adaptive behaviors such as resource foraging. Moreover, betting amounts increased slightly but reliably when gamblers followed trends. These findings provide new insights into cognitive biases in gambling, challenge established theories of positive and negative recency, and underscore the importance of considering the unique structural characteristics of specific games when studying gambling behavior. This perspective may also contribute to a deeper understanding of pathological and problem gambling.